The Role of the State in the Process of Economic Development Communication - Iwan Armawan; La Dono (JKEN: Jurnal Kajian Ekonomi Nasional, 2026)
Abstract                                                                                     This study aims to analyze and conceptualize the multifaceted role of the state in the process of economic development through a qualitative, descriptive, and literature-based approach. The research employs secondary data derived from academic journals, theoretical works, and official reports, analyzed through thematic coding and inductive synthesis to identify conceptual patterns and interconnections. The findings reveal that the effectiveness of the state in driving economic growth depends not on the scale of intervention but on institutional quality, fiscal capacity, and governance integrity. The study identifies four core dimensions of the state’s role: (1) the developmental function, where bureaucratic autonomy and coherent industrial policy support structural transformation; (2) fiscal and administrative capacity, which underpins the state’s ability to finance public goods; (3) the ethical and distributive role, as emphasized in Islamic economic frameworks advocating justice and sustainability; and (4) the cooperative interaction between the state and the market in fostering innovation and inclusive growth. These findings suggest that the modern state must act as both a developmental and normative agent, balancing economic efficiency with social equity. The study contributes to academic discourse by synthesizing developmental state theory, institutional economics, and moral-economic perspectives, offering an integrative framework for understanding the adaptive and ethical functions of the state in contemporary economic systems.   Keywords: State capacity, governance, developmental state, economic transformation, fiscal policy